Toward Efficiency Public Policy : Lessons from the Uzbekistan’s UzIMEI System - Dilbarova, Malika; Hamza, Ali; Khan, Ebrima; Kumalasari, Ana (Universitas Bojonegoro, 2025)
This study critically examines the UzIMEI system—Uzbekistan’s mobile device registration and customs policy—through the lens of public administration, focusing on policy efficiency, digital governance, and social equity. Implemented in 2024, the UzIMEI system aimed to formalize imports and improve tax compliance. However, it has encountered significant operational challenges, including manual processing delays, a flat-rate fee structure that disproportionately burdens low-income users, and limited public awareness. Using a literature review methodology, this paper evaluates the administrative shortcomings of UzIMEI and draws comparative insights from international best practices in Indonesia, India, and Kenya. These countries have adopted digital automation, tiered taxation, and public outreach campaigns to improve policy compliance and public service delivery. The analysis highlights that effective public policy must balance efficiency with equity and transparency. The study concludes that a hybrid reform model—comprising digital system integration, progressive fee structures, and citizen engagement strategies—offers the most viable path forward. By implementing such reforms, Uzbekistan can enhance both the effectiveness and fairness of its public services, positioning itself as a leader in equitable digital governance. This research contributes to the broader discourse on digital transformation and inclusive policy-making in emerging public administration contexts.